Foot and ankle minimally invasive surgery what’s up? - Younger, Alastair (Journal of the Foot & Ankle, 2026)
Minimally invasive surgery has become much more prevalent in foot and ankle surgery. The rate of publication has increased dramatically, and there is considerable interest in minimally invasive surgery. There are both proponents and critics, as well as benefits and potential complications. In this article, a review of the current literature on the evidence for and against minimally invasive surgery was conducted to present a balanced argument. I will also summarize my personal experience so that, upon reading this article, surgeons have a better understanding of why I have made this change and continue to evaluate outcomes, risks, and benefits. Level of evidence I; Therapeutic studies - investigating the results of treatment.